Implementasi Kebijakan Kelas Rawat Inap Standar Jaminan Kesehatan Nasional (KRIS-JKN) di RSUD Kota Bandung - Sudrajat, Achmad Sodik; Hanifah Rahayu, Rifa (Journal of Governance Innovation, 2025)
This study describes the implementation of the National Health Insurance Standard Inpatient Class (KRIS-JKN) policy at the Bandung City Hospital. This study uses a descriptive qualitative approach using in-depth interview techniques based on the Van Meter and Van Horn policy implementation model. Inpatient room facilities, especially for BPJS Kesehatan Class 3 patients, require special attention because they are not standardised. RSUD Kota Bandung as one of the government-owned hospitals is obliged to support the KRIS-JKN policy, but the update as of July 2024 the percentage of indoor beds that have fulfil 12 KRIS criteria is only 15.87%. Bandung City Hospital experienced several obstacles, including the distance between TT less than 1.5m, bathrooms not in accordance with accessibility standards, and curtain replacement. Budget limitation is the main factor that hinders the implementation of KRIS. Therefore, efforts are needed to strengthen KRIS-JKN regulations in Bandung City as well as funding support from the Bandung City Government APBD.